Fetal Abdominal Circumference Growth in Bangladeshi Population - Rashid, Sabrina Q (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: Fetal abdominal circumference is the single most important parameter for determining fetal growth. Determination of fetal growth abnormalities will be more accurate if we use tables prepared on our own population. A nomogram of fetal abdominal circumference in Bangladeshi population is therefore presented in this study. Methods: A prospective, cross-sectional study was conducted on well dated, singleton pregnancies. A table and a graph were prepared after fitting Polynomial regression models. Results: Fetal charts were constructed from1223 subjects. 3rd, 10th, 50th, 90th and 97th percentiles, mean and standard deviations were derived. The models showed good fit to the data. There was a gradual increase of the abdominal circumference measurements up to 37th week. Standard deviations showed increased variability as the pregnancy advanced. In the early second trimester Bangladeshi, Indian, and western measurements were similar but as pregnancy advanced there was variation between different races especially from the western. Conclusion: These findings suggest that this chart is unique for Bangladeshi population and can be useful for accurate assessment of fetal growth, especially in the 3rd trimester. Key words: abdominal circumference, fetal growth, Bangladesh. DOI: 10.3329/jbcps.v26i3.4195 J Bangladesh Coll Phys Surg 2008; 26: 124-127